OsDXR interacts with OsMORF1 to regulate chloroplast development and the RNA editing of chloroplast genes in rice - Peng-hui CAO; Di WANG; Su GAO; Xi LIU; Zhong-ying QIAO; Yu-lin XIE; Ming-hui DONG; Tan-xiao DU; Xian ZHANG; Rui ZHANG; Jian-hui JI (Journal of Integrative Agriculture, 2023)
Plant chlorophyll biosynthesis and chloroplast development are two complex processes that are regulated by exogenous and endogenous factors. In this study, we identified OsDXR, a gene encoding a reductoisomerase that positively regulates chlorophyll biosynthesis and chloroplast development in rice. OsDXR knock-out lines displayed the albino phenotype and could not complete the whole life cycle process. OsDXR was highly expressed in rice leaves, and subcellular localization indicated that OsDXR is a chloroplast protein. Many genes involved in chlorophyll biosynthesis and chloroplast development were differentially expressed in the OsDXR knock-out lines compared to the wild type. Moreover, we found that the RNA editing efficiencies of ndhA-1019 and rpl2-1 were significantly reduced in the OsDXR knock-out lines. Furthermore, OsDXR interacted with the RNA editing factor OsMORF1 in a yeast two-hybrid screen and bimolecular fluorescence complementation assay. Finally, disruption of the plastidial 2-C-methyl-derythritol-4-phosphate pathway resulted in defects in chloroplast development and the RNA editing of chloroplast genes.